In-situ characterization of heterogeneous catalysts - Rodríguez, José A.; Hanson, Jonathan C.; Chupas, Peter J. (Wiley, 2013)
"This book describes innovative techniques to study catalysts and reaction mechanisms, helping chemists improve the performance of their reactions and the efficiency (through reduced materials and waste) of catalyst preparation. It explains both the scope and limitations of specific techniques, including the characterization of the electronic and structural properties of catalysts using XAFS (X-ray Absorption Fine Structure Spectroscopy); techniques for structural characterization based on X-ray diffraction and scattering; for microscopy and morphological studies; for studying the interaction of adsorbates with catalyst surfaces (Raman spectroscopy, NMR, moderate pressure XPS); and mixed techniques"--